Classification of Nostoc-like cyanobacteria isolated from paddy soil into Aliinostoc, Aulosira, and Desmonostoc - Pham, Hang T. L.; Ngo, Trang T.; Tran, Thang V.; Duong, Tuan A.; Tran, Long D.; Tran, Anh T. T.; Nguyen, Van T. H.; Nguyen, Sang V. (Frontiers in Microbiology, 2025)
Accurate identification of cyanobacterial strains is an essential step for subsequent research to be performed on these organisms. The classification of cyanobacteria in Nostocaceae remains a significant challenge due to the lack of reference data for type species and robust morphological characters for each genus. This study aims to classify 38 new isolated Nostoc–like strains at the genus level. The relationship between phylogenetic classification and morphological characteristics at the genus level was also investigated. The 16S rRNA gene sequences served as primary data for phylogenetic classification, supporting the designation of 18 isolates into the Aliinostoc, 7 isolates into the Aulosira, and 13 isolates into the Desmonostoc. Subsequently, we used these isolates as living materials to discover the most distinct features at each genus level of Aliinostoc, Aulosira, and Desmonostoc. As a result, the morphological characteristics of the three genera became distinguishable when grown in the BG110 medium. There, the mature vegetative cells of all isolated strains in the Aliinostoc were gray or brown, the strains in the Aulosira exhibited basal heterocysts at the beginning of cultivation, and the Desmonostoc strains showed the appearance of akinetes in the life cycle as an alternative reproduction. All isolated strains exhibited heterocysts, indicating their ability to fix nitrogen and potentially improve nutrient availability in paddy soil, especially in nitrogen-deficient conditions. This study provides a dataset of 16S rRNA gene sequences and morphological characteristics of Nostoc morphotypes, contributing to cyanobacterial taxonomy.